Coordination Functions of Electricity Price Providing Locational Signals under the Circumstance of Electricity Spot Market - Lizi ZHANG; Ye CONG; Wenbin TAO; Fukang ZHENG; Zhengfei CHEN (Zhongguo dianli)
The paper investigates the locational signals of the electricity prices and the pricing mechanisms which can provide locational signals, and analyzes the functions of locational signals of electricity prices under the circumstance of electricity spot market. Based on simulation of electricity spot market, the paper quantitatively analyzes the coordination functions of location marginal pricing (LMP) mechanism and zonal transmission pricing mechanism in realizing their pricing role as public utilities under different network structures and system congestion conditions. According to the actual conditions of a provincial power grid in China, a case study was carried out to verify the analysis results through transmission price calculation and electricity spot market simulation. Suggestions are provided for selection of electricity pricing mechanism under the circumstance of electricity spot market in China.